Quasi-Spherical Cell Clusters Induced by a Polyelectrolyte Multilayer - Arias, Carlos J (Langmuir : the ACS journal of surfaces and colloids, 2015)
Fibroblasts cultured on polyelectrolyte multilayers, PEMUs, made from poly(diallyldimethylammonium), PDADMA, and poly(styrene sulfonate), PSS, showed a variety of attachment modes, depending on the charge of the last layer and deposition conditions. PEMUs terminated with PDADMA (cationic) were cytotoxic when built in 1.0 M NaCl but cytophilic when built in 0.15 M NaCl. Cells adhered poorly to all PSS-capped (anionic) films. PEMUs built in 0.15 M NaCl but terminated with a layer of PSS in 1.0 M NaCl induced most cells to form spherical clusters after about 48 h of culture. These clusters still interrogated the surface, and when they were replated on control tissue culture plastic, cells emerged with close to 100% viability. Differences between the various surfaces were probed in an effort to identify the mechanism responsible for this unusual behavior, which did not follow accepted correlations between substrate stiffness and cell adhesion. No significant differences in roughness or wetting were observed between cluster-inducing PSS-capped multilayers and those that did not produce clusters. When the surface charge was assayed with radiolabeled ions a strong increase in negative surface charge was revealed. Viewing the multilayer as a zwitterionic solid and comparing its surface charge density to that of a cell membrane yields similarities that suggest a mechanism for preventing protein adhesion to the surface, a necessary step in the integrin-mediated mechanotransduction properties of a cell